Self-esteem and maternal socialization: a transcultural analysis - González-Arratia, Norma Ivonne (2006)
Self-concept and self-esteem are two basic concepts that explain an individual’s successful functioning and adaptation in her environment. Additionally, culture, social stratification, and family system constitute causal agents in the process of socialization. In this process of development, maternal figures become an important source of transmission of differential values and positive self-evaluation for their children. In this article, from a psycho-social perspective, the cultural influence of maternal figures is analyzed. A comparison between characteristics both mothers and children from samples of Spain and Mexico is made.